Corrigendum - Prospective study of Medication Adherence Pattern in Chronic Obstructive Pulmonary Disease and Asthma Patients in Tertiary care Teaching Hospital (Indian Journal of Pharmacy Practice)
The article published titled “Prospective study of Medication Adherence Pattern in Chronic Obstructive Pulmonary Disease And Asthma Patients in Tertiary care Teaching Hospital” in Indian Journal of Pharmacy Practice, Vol 8, Issue 2, Apr-Jun, 2015 with page numbers 78-83 “Morisky Medication Adherence Scale” to be read as Medication Adherence Scale and Inhaler Adherence Scale, A prototype scale based on Morisky Medication Adherence scale”